ROBLEMATIKA PELESTARIAN BAHASA DAERAH SEBAGAI KEARIFAN LOKAL DI TENGAH MASYARAKAT MULTIKULTURAL DESA ILATH MALUKU - Enda Tomia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The decline in the use of regional languages ​​due to modernization and globalization threatens the inheritance of local wisdom and cultural identity in Ilath Village, Maluku, a multicultural community consisting of Buton, Bugis, and Buru ethnic groups. This study aims to analyze the main factors causing the decline in the use of regional languages ​​and examine their impact on local wisdom-based moral education from an Islamic perspective. This study uses a descriptive qualitative approach, with primary data collected through in-depth interviews with traditional leaders and the younger generation, and analyzed using the Miles and Huberman interactive model with source triangulation. The results indicate that the root causes include: the weakening role of the family, a multicultural social environment that uses the Ambonese Malay dialect, a lack of formal educational support, and the rapid influence of digital media, which collectively cause the erosion of local wisdom and traditional moral values. Preservation efforts are now being carried out through initiatives from families, educational institutions, religious leaders, and the village government. Therefore, the preservation of regional languages ​​is crucial for maintaining cultural identity and Islamic values ​​and needs to be effectively integrated into character education.